Context and Pedagogy as Signpoints to Authentic Learning Paths - Meriläinen, Merja; Piispanen, Maarika (International Electronic Journal of Elementary Education, 2023)
In the Finnish National Core Curriculum for Basic Education (2014), the conception of language is based on the communal and functional linguistics model of language. From the perspectives of teaching and learning, this requires that learning contexts and pedagogies enable learning in such learning environments, roles, and processes where the pupil can think and act authentically, according to his or her age (OPS 2014, 287). Thus, in this article we examine the integration of subject teaching with topic teaching in the frameworks of sociocultural learning, functional linguistics, and authentic learning, in the contextual-pedagogical learning landscape, where the individuality of learners as well as timely learning support (scaffolding) in the zone of proximal development (Vygotsky 1978) enable the learning of contents as part of multidisciplinary learning. The subject Finnish language and literature is defined as a multidisciplinary, practical, theoretical, and cultural subject (OPS 2014, 160) that requires cooperation with other subjects. The article sheds light on a perspective on multidisciplinary learning, where the topic studied gives meaning to the subject-related contents, and where the ability to acquire the core contents of the subject related to the topic studied form a prerequisite for the processing of the topic.